2017
DOI: 10.3897/natureconservation.18.11523
|View full text |Cite
|
Sign up to set email alerts
|

Pollination services mapping and economic valuation from insect communities: a case study in the Azores (Terceira Island)

Abstract: Insect pollinators provide vital ecosystem services through its maintenance of plant biological diversity and its role in food production. Indeed, adequate pollination services can increase the production and quality of fruit and vegetable crops. This service is currently challenged by land use intensification and expanding human population growth. Hence, this study aims: (1) to assess the pollination services in different land uses with different levels of disturbance through GIS mapping technique using insec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 71 publications
1
18
0
1
Order By: Relevance
“…This attracted many pollinating bees, butterflies, and hoverflies to invaded areas, even when plots had relatively low flower densities. These results are consistent with previous studies that revealed when the invasive plant is a pollination generalist (native) nectarivores can be tempted to pollinate the invader (Bartomeus et al, 2008; Picanço, Gil, Rigal, & Borges, 2017; Traveset & Richardson, 2006). While we anticipated A. leptopus to disrupt obligate plant–herbivore interactions and thus cause a reduction in herbivore abundance (e.g., Hartley, Rogers, & Siemann, 2010), we observed an unexpected increase in herbivore abundance.…”
Section: Discussionsupporting
confidence: 93%
“…This attracted many pollinating bees, butterflies, and hoverflies to invaded areas, even when plots had relatively low flower densities. These results are consistent with previous studies that revealed when the invasive plant is a pollination generalist (native) nectarivores can be tempted to pollinate the invader (Bartomeus et al, 2008; Picanço, Gil, Rigal, & Borges, 2017; Traveset & Richardson, 2006). While we anticipated A. leptopus to disrupt obligate plant–herbivore interactions and thus cause a reduction in herbivore abundance (e.g., Hartley, Rogers, & Siemann, 2010), we observed an unexpected increase in herbivore abundance.…”
Section: Discussionsupporting
confidence: 93%
“…Twenty out of the 34 studied species are known from at least four islands and many of them are widely distributed within each island. These common species include all eight Crambidae, which are important pollinators of the Azorean native forest (Picanço et al 2017). …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is still limited information on the condition of pollinators and the related ecosystem services they provide in oceanic islands, although recent research has demonstrated that insect pollinators play a key role in agricultural production [ 29 ]. Previous studies have shown that oceanic insular ecosystems usually support less complex pollination networks with lower numbers of pollinator species, and that these mostly comprised generalist species [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%